Granulomatosis with polyangiitis: mind the airway. Issue 1 (21st December 2020) - Oqueka, Tim; Klose, Hans; Iking‐Konert, Christof; Schnoor, Ulrike; Kluge, Stefan; Simon, Marcel
Key message: Granulomatosis with polyangiitis (GPA) is a potentially life‐threatening disease that affects all ages. As the disease may be rapidly progressive, the undelayed recognition of its inflammatory activity is critical. This is especially important in central airway involvement, which contributes to morbidity and mortality. Abstract : We present the case of a 17‐year‐old boy with granulomatosis with polyangiitis (GPA) with central airway involvement.